2019
DOI: 10.1111/bcp.13863
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b randomized, placebo‐controlled clinical trial with SNF472 in haemodialysis patients

Abstract: Aims: SNF472 is a calcification inhibitor that is being studied as a novel treatment for calciphylaxis and cardiovascular calcification (CVC). A first study showed acceptable safety and tolerability in a single ascending dose administration in healthy volunteers and a single dose administration in haemodialysis (HD) patients. This study aimed to assess the safety, tolerability, and pharmacokinetics/pharmacodynamics relationship of intravenous SNF472 in HD patients in a multiple ascending dose administration tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 32 publications
5
17
0
Order By: Relevance
“…Chelation of ionized calcium by 50% in saline occurred at SNF472 concentrations of 539 μM, nearly 50-fold greater than concentrations that inhibited hydroxyapatite crystallization in adapted synthetic fluid and >40-fold greater than free concentrations of SNF472 associated with a single dose of 9 mgÁkg −1 in the phase 1 clinical trial described above (Perelló et al, 2018). Doses of SNF472 in clinical development to treat cardiovascular calcification or calcific uraemic arteriolopathy (Brandenburg et al, 2019;Raggi et al, 2020) are not expected to chelate circulating calcium and hypocalcaemia was not reported in the phase 1b trial (Salcedo et al, 2019 In 157 postmenopausal women, those with low (≤0.76 μM) phytate concentrations had significantly greater bone mass loss in the lumbar spine than those with high (≥1.42 μM) phytate concentrations (López-González et al, 2013). In our experiments, the 9-month repeated dosing toxicology study in dogs showed no differences in full bone histomorphology or tartrate-resistant acid phosphatase, an osteoclast biomarker, between control animals and animals treated with SNF472.…”
Section: Effects Of Snf472 On In Vitro Osteoblast Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelation of ionized calcium by 50% in saline occurred at SNF472 concentrations of 539 μM, nearly 50-fold greater than concentrations that inhibited hydroxyapatite crystallization in adapted synthetic fluid and >40-fold greater than free concentrations of SNF472 associated with a single dose of 9 mgÁkg −1 in the phase 1 clinical trial described above (Perelló et al, 2018). Doses of SNF472 in clinical development to treat cardiovascular calcification or calcific uraemic arteriolopathy (Brandenburg et al, 2019;Raggi et al, 2020) are not expected to chelate circulating calcium and hypocalcaemia was not reported in the phase 1b trial (Salcedo et al, 2019 In 157 postmenopausal women, those with low (≤0.76 μM) phytate concentrations had significantly greater bone mass loss in the lumbar spine than those with high (≥1.42 μM) phytate concentrations (López-González et al, 2013). In our experiments, the 9-month repeated dosing toxicology study in dogs showed no differences in full bone histomorphology or tartrate-resistant acid phosphatase, an osteoclast biomarker, between control animals and animals treated with SNF472.…”
Section: Effects Of Snf472 On In Vitro Osteoblast Calcificationmentioning
confidence: 99%
“…Using a pharmacodynamic assay to measure the crystal formation potential of blood (Ferrer et al, 2017), (Salcedo et al, 2019). Maximum SNF472 concentration was 101 μM for a single dose of 20 mgÁkg −1 and 62.9 μM after 12 doses of 10 mgÁkg −1 (Salcedo et al, 2019). Thus, concentrations of SNF472…”
Section: Effects Of Snf472 On In Vitro Osteoblast Calcificationmentioning
confidence: 99%
“…Results from plasma samples in rats and humans (with or without dialysis) validated the assay to measure inhibition of crystallization in the presence of polyphosphates, fetuin-A, sodium thiosulfate, and SNF472 15 . A phase 1b trial of SNF472 in patients undergoing dialysis provided further evidence supporting the ability of the assay to detect inhibition of calcium phosphate crystallization 14 .…”
mentioning
confidence: 89%
“…In vitro studies showed that at a concentration of 30 mg/L (45.5 μM) or above, SNF472 concentrations increase in blood while infused, reach a plateau, and remain nearly constant during dialysis 12 . Phase 1 and 2a clinical trials also showed that SNF472 was not dialyzable when it was infused during the dialysis session at doses ranging from 3 to 20 mg/kg 13,14 .…”
mentioning
confidence: 99%
“…SNF472 inhibited CV calcification in adenine-induced CKD rats by up to 90% (Table 2) [20]. In ex vivo analysis using plasma from HD patients, hydroxyapatite crystallization potential was reduced by SNF472 [101,102]. The first phase 2 study CaLIPSO with 274 HD patients demonstrated attenuated progression of CAC and aortic valve calcification compared to placebo control, after 52 weeks of SNF472 treatment [21].…”
Section: Hexasodium Salt Of Myo-inositol Hexaphosphatementioning
confidence: 99%